Willingness to pay and price elasticity of demand for long-acting injectable cabotegravir among men who have sex with men in Guangxi, China - Shiwen Chen; Yuhua Ruan; Lu Liu; Hengyan Pei; Yu Jiang; Tengda Huang; Yuxia Wei; Litai Qin; Xuebin Dai; Yu Liu; Junhui Liu; Yihong Xie (Frontiers Media S.A., 2024)
ObjectivesThere is still no study focused on willingness to pay for long-acting injectable cabotegravir (CAB-LA) after it was available on the market in the United States in 2021. Here, we explored the willingness to pay for CAB-LA and associated factors and price elasticity of demand (PED) of CAB-LA among men who have sex with men (MSM) in Guangxi, China.MethodsA cross-sectional study was conducted. Univariate and multivariate ordinal logistic regression analyses were performed to explore the associated factors of willingness to pay for CAB-LA. PED was used to measure the change in the number of participants willing to pay to a change in price.ResultsA total of 1,006 MSM were recruited, among which 84.1% were aged between 18 and 39 years old. The median (interquartile) of the maximum amount of willing to pay for CAB-LA was 200 (100-500) Chinese yuan (CNY) per month. Most (84.2%) were willing to pay less than 600 CNY per month. The number of participants willing to pay for CAB-LA significantly increased with decrease in the price. When the price (CNY per month) decreased from 600 to 500, 500 to 400, 400 to 300, and 300 to 200, PED was 3.13, 1.64, 1.33, and 1.17, respectively. The maximum amount of willing to pay for CAB-LA was positively associated with younger age (vs. ≥40 years group, 18-24 years group, aOR: 1.94, 95% CI: 1.32-2.85; 25-39 year group, aOR: 1.70, 95% CI: 1.20-2.42), being high educated (vs. middle school or lower group, high school or college group, aOR: 1.61, 95% CI: 1.06-2.48; bachelor's degree or above group, aOR: 2.21, 95% CI: 1.41-3.49), monthly income ≥6000 CNY (vs. <3000 CNY, aOR: 1.46, 95% CI: 1.02-2.09), being bisexual/unsure sexual orientation (vs. gay, aOR: 1.73, 95% CI: 1.24-2.43), and heard of PrEP and used (vs. never heard of PrEP, aOR: 1.76, 95% CI: 1.11-2.77).ConclusionThe maximum amount of willing to pay for CAB-LA was low in Guangxi, China. PED of CAB-LA is relatively elastic. The waived patent protection should be considered for the wide promotion of CAB-LA, and the health education should be strengthened to improve the recognition of CAB-LA.